Dividend policy issues in the European pharmaceutical industry: new empirical evidence - Tobias Basse; Christoph Schwarzbach; J.-Matthias Graf von der Schulenburg (The European Journal of Health Economics, 2022)
This paper examines dividend policy issues in the European pharmaceutical industry. This sector is of particular interest because of the high research and development expenditures and the associated risks characterizing the business models of many firms in this industry. In fact, from the perspective of corporate finance theory, this is a particular challenge for the managers of these corporations that may also have implications for the dividend policy implemented by the firms forming this sector. Moreover, the level of internal financing and litigation risks also seem to be high in the pharmaceutical industry. These facts could also affect the payout policy of the firms. Employing techniques of time series analysis, there is no evidence for dividend signaling and clear evidence for dividend smoothing in the European pharmaceutical industry. Given that dividend increases under certain assumptions can negatively affect the firms' ability to finance new investments in general and research and development projects in particular, these results of our empirical investigations could be described as highly plausible.
Keywords: G35; L65; K41; O32; O34; 610; Dividend policy; Granger causality; Pharmaceutical industry; Health care firms; Research and development expenditures; Litigation risk